Second generation catalytic enantioselective nucleophilic desymmetrization at P(V): improved generality, efficiency and modularity - Formica, M; Ferko, B; Marsh, T; Davidson, TA; Yamazaki, K; Dixon, DJ (Wiley, 2024)
A broadly improved second generation catalytic two-phase strategy for the enantioselective synthesis of chiral at phosphorus (V) compounds is described. This protocol, consisting of a bifunctional iminophosphorane (BIMP) catalyzed nucleophilic desymmetrization of prochiral, bench stable P(V) precursors and subsequent enantiospecific substitution allows for divergent access to a wide range of C-, N-, O- and S- substituted P(V) containing compounds from a handful of enantioenriched precursors. A new ureidopeptide BIMP catalyst/thiaziolidinone leaving group combination allowed for a far wider substrate scope and increased reaction efficiency and practicality over previously established protocols. The resulting enantioenriched intermediates could then be transformed into an even greater range of distinct classes of P(V) compounds by displacement of the remaining leaving group as well as allowing for even further diversification downstream. Density functional theory (DFT) calculations were performed to pinpoint the origin of enantioselectivity for the BIMP-catalyzed desymmetrization, to rationalize how a superior catalyst/leaving group combination leads to increased generality in our second-generation catalytic system, as well as to shed light onto observed retention and inversion pathways when performing late-stage enantiospecific SN2@P reactions with Grignard reagents.